A peteca, o campo do lazer e a dinâmica urbana de Belo Horizonte (1980 1994) - Renato Machado dos Santos (2011)
This research has as its main focus the study of a pleasing activity of the dwellers of Belo Horizonte that is still unusual in the academic field. On this subject, we have as a goal the analysis of Peteca (a game played on a court in which bare hands are used to volley a feather shuttlecock over a net) in the city between 1980s and 1990s, starting from what is considered one of the best places to practice, Campo do Lazer (Leisure Place). The goal was defined into the basis of helping the retrieval and reflection about the memory of Peteca and Campo do Lazer throughout historical research, based on testimonies, allowing the entry and the elaboration of a document. In order to frame an analysis referential, a bibliographical and documental survey was made. Articles, thesis and essays related to leisure and modern sport formation were analyzed. The critical review was based on authors who cover urban places in dialogue with others who focus their study on leisure. Taking into consideration the deficit of records related to Campo do Lazer and the path of the practice of Peteca during the mentioned period of time, it was needed an exploratory like effort to search for sources and accuracy for sorting out and reading newspapers, magazines, images and others. Facing an obscurity of facts due to the absence of documentation, the Oral History methodology was attempted. Therefore it is causal concern of this research, on account of information resulting from documental sources, to make new publications through oral reference. This fact raised the importance of participants oral memory who took part of their history somehow. Past facts occurred before Campo do Lazer was built help us understand not only how it was put into service by the Peteca players, but also to realize its role for getting people together to play this sport in those mentioned decades, spreading influences of it throughout the city.